Visualizing Microorganism-Mineral Interaction in the Iberian Pyrite Belt Subsurface: The Acidovorax Case - Escudero, Cristina; del Campo, Adolfo; Ares, Jose R.; Sánchez, Carlos; Martínez, Jose M.; Gómez, Felipe; Amils, Ricardo (Frontiers in Microbiology, 2020)
Despite being considered an extreme environment, several studies have shown that life in the deep subsurface is abundant and diverse. Microorganisms inhabiting these systems live within the rock pores and, therefore, the geochemical and geohydrological characteristics of this matrix may influence the distribution of underground biodiversity. In this study, correlative fluorescence and Raman microscopy was used to analyze the mineralogy associated with the presence of members of the genus Acidovorax, an iron oxidizing microorganisms, in native rock samples of the Iberian Pyrite Belt subsurface. Our results suggest a strong correlation between the presence of Acidovorax genus and pyrite, suggesting that the mineral might greatly influence its subsurface distribution.